Vertical fire: For a pyropolitics of the subsurface. Issue 127 (December 2021) - Clark, Nigel
Highlights: Use of fire enables surface dwelling humans to access the Earth's subsurface. Early human fire use linked to evolution in tectonically active landscapes. Mineral extraction and chambered fire underpin political power in ancient city-states. Gunpowder and explosive weapons crucial to expansion of early modern empires. Climate change calls for new ways of using fire to negotiate the subsurface. Abstract: The geopolitical - or more specifically pyropolitical – crisis triggered by combusting fossilized hydrocarbons can be viewed in the context of a much longer human history of utilising fire as a means of traversing and utilising the Earth's subsurface. The paper develops a conceptual framework to show how the developing fire-subsurface nexus advances through a succession of different human enfoldings or 'involutions' of fire that serve to intensify its force. This is explored at three critical junctures: the earliest hominin uses of fire in the geologically active landscape of the Great Rift Valley, the chambering of fire by ancient artisans and the material and political significance of its products in emergent city-states, and the role of explosive weapons in gunpowder empires. Finally, the paper circles back on the question of how revisiting the longue durée of human fire-subsurface entanglements might help us conceive of alternative pyropolitical realities.